2007
DOI: 10.1007/s12034-007-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Film adhesion in amorphous silicon solar cells

Abstract: A major issue encountered during fabrication of triple junction a-Si solar cells on polyimide substrates is the adhesion of the solar cell thin films to the substrates. Here, we present our study of film adhesion in amorphous silicon solar cells made on different polyimide substrates (Kapton VN, Upilex-S and Gouldflex), and the effect of tie coats on film adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Within the framework of the ROSA (Roll-Out Solar Array) project, a flexible roll-up solar panel was tested on the International Space Station and it was shown that for a cell with a power of 15 kW, a weight reduction is up to 33% and usable space can be saved up to is 75%, in comparison with folded rigid panels of the same capacity [ 7 ]. To date, there are many approaches to the creation of flexible cover glasses based on polyamides [ 8 , 9 , 10 ], various polysiloxanes [ 11 , 12 , 13 ] and composites based on them [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within the framework of the ROSA (Roll-Out Solar Array) project, a flexible roll-up solar panel was tested on the International Space Station and it was shown that for a cell with a power of 15 kW, a weight reduction is up to 33% and usable space can be saved up to is 75%, in comparison with folded rigid panels of the same capacity [ 7 ]. To date, there are many approaches to the creation of flexible cover glasses based on polyamides [ 8 , 9 , 10 ], various polysiloxanes [ 11 , 12 , 13 ] and composites based on them [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such advances were permitted with development of microfabrication, which enable one to realize fine features as small as a submicron length. Such sensors can play a crucial role in detailed examination of adverse flow condition, as in phase change application for instance, which can be achieved by its instantaneous measurement at multipoint resolution and its conformity to nonplanar surfaces [11][12][13][14]. Among the various works on resistive sensors, is the one done by Guereca [15] in the field of microelectromechanical systems, which was used in boiling application.…”
Section: Resistive Based Sensorsmentioning
confidence: 99%
“…3b. 41 Although the mechanical strength and thermal stability of polymers are not comparable with that of metal foils, high efficiency devices have also been realized. 32,42,43 Fuji Electric developed a-Si:H/a-SiGe:H based tandem solar cells on plastic substrate and achieved a stabilized efficiency of 9% in a 40 cm  80 cm cell.…”
Section: Flexible Thin Lm A-si:h/mc-si:h Solar Cellsmentioning
confidence: 99%